Tissue cholesterol metabolism and prostate cancer aggressiveness: Ethno‐geographic variations. Issue 16 (13th September 2021) - Lethongsavarn, Vincent; Pinault, Michèle; Diedhiou, Abdoulaye; Guimaraes, Cyrille; Guibon, Roseline; Bruyère, Franck; Mathieu, Romain; Rioux‐Leclercq, Nathalie; Multigner, Luc; Brureau, Laurent; Fournier, Georges; Doucet, Laurent; et al.
Abstract: Background: Prostate cancer (PCa) is more frequent and more aggressive in populations of African descent than in Caucasians. Since the fatty acid composition of peri‐prostatic adipose tissue (PPAT) has been shown to differ according to the ethno‐geographic origin and is involved in PCa aggressiveness, we aimed to analyze the cholesterol content of PPAT from Caucasian and African‐Caribbean patients, in correlation with markers of disease aggressiveness and cholesterol metabolism in cancer tissues. Methods: The quantification of cholesterol in PPAT was analyzed in 52 Caucasian and 52 African‐Caribbean PCa patients, with in each group 26 indolent tumors (ISUP Group1 and pT2) and 26 potentially aggressive tumors (ISUP Group 3–5 and/or pT3). The expression of proteins involved in cholesterol metabolism was analyzed by immunohistochemistry on cancer tissue samples included in tissue microarrays. Results: The amount of cholesterol esters was lower in PPAT from African‐Caribbean patients compared with Caucasians, without any correlation with markers of disease aggressiveness. In cancer tissues from African‐Caribbean patients, the expression of ABCA1 (involved in cholesterol efflux) was decreased, and that of SREBP‐2 (involved in cholesterol uptake) was increased. In both groups of patients, SREBP‐2 expression was strongly associated with that of Zeb1, a key player in the epithelial‐to‐mesenchymal transition (EMT) process. Conclusion: These results suggest that cholesterol metabolism differs according to the ethno‐geographic origin, in both PPAT and cancer tissues. In African‐Caribbeans, the orientation towards accumulation of cholesterol in cancer cells is associated with a more frequent state of EMT, which may promote PCa aggressiveness in this population.